Integrated Learning System Between Reading the Yellow Book and Memorizing the Qur'an in Islamic Boarding Schools: Case Study at the Baitul Abidin Darussalam Wonosobo Tahfidzul Qur'an Islamic Boarding School - Farich Ahsani; Abdurrahman Al-Asy’ari; Samsul Munir Amin; Salis Irvan Fuadi; Moh. Sakir; Feni Nur Afifah (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
Islamic boarding schools (Islamic boarding schools) are required to integrate classical scholarly traditions and modern education, one way of doing this is through the integration of the study of yellow books (tahfidzul Qur'an) and Qur'an memorization (tahfidzul Qur'an). The Baitul Abidin Darussalam Wonosobo Tahfidzul Qur'an Islamic Boarding School implements an integrative learning system to balance Qur'an memorization and understanding of Islamic law (shari'a). However, it still faces obstacles such as a tight schedule, different methods, and weak coordination and evaluation. This study examines the implementation patterns, challenges, and impacts of this system, with the hope of serving as a reference for developing a balanced and sustainable model of Islamic boarding school education. This research uses a qualitative approach with a case study design to understand in-depth the implementation of the integrative learning system between Qur'an memorization and the study of yellow books (tahfidzul Qur'an) at the Baitul Abidin Darussalam Wonosobo Islamic Boarding School (PPTQ). Subjects were selected purposively, including the boarding school administrator, tahfidz teachers, yellow book teachers, and students. Data were collected through in-depth interviews, participant observation, and documentation studies. Data analysis was conducted interactively using the Miles and Huberman model, which encompasses data reduction, data presentation, and conclusion drawing and verification to obtain a holistic and contextual understanding. The discussion shows that the integrative learning system in Islamic boarding schools is implemented through a balanced daily schedule between Quran memorization and yellow book study, allowing memorization, understanding, and moral development to occur simultaneously within the students' daily routines. Integration is achieved structurally through scheduling, methodologically by linking verse memorization with book study, and culturally through the instillation of values, etiquette, and pesantren traditions. The success of integration is supported by the exemplary behavior of the kiai (Islamic teachers) and ustadz (Islamic teachers), the religious environment, and the motivation and discipline of the students, despite challenges such as busy schedules, physical exhaustion, differences in student abilities, and limited facilities. The impact of implementing this system is seen in the improved quality of contextual memorization, a more critical understanding of the scriptures, the formation of disciplined and moral character, and the holistic spiritual development of students.